1998
DOI: 10.1021/jo9810718
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclization of Enynes Using the Cp2TiCl2−Mg−BTC System:  A Practical Method to Bicyclic Cyclopentenones

Abstract: Bicyclic titanacycles 2 generated with the Cp 2 TiCl 2 -Mg-P(OEt) 3 system can be trapped with bis-(trichloromethyl) carbonate (BTC) to give bicyclic cyclopentenones 3 in good yields. The titanacycle 2m was isolated and well-identified. Bicyclization of enynes containing 1,2-disubstituted olefin by this method gave good results with excellent stereoselectivity.a Method A: CO, M ) Ti, Zr. Method B: R3SiCN, then HOAc or CuSO4, M ) Ti.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 38 publications
(38 reference statements)
0
18
0
Order By: Relevance
“…Scheme 3 As shown in Scheme 3, endo-norbornene ester 9 was prepared by a thermal Diels-Alder reaction of 1-methyl-cyclopentadiene 8 [17] with maleic anhydride, followed by sub-sequent esterification. of Co 2 (CO) 8 atures (120°C) resulted in further increase in the selectivity (12e/13e 12:88, entry 11). [20] Norbornene ester 9 was then employed in NMO-promoted Pauson-Khand reactions with terminal alkynes 11 to give regioisomeric enones 12 and 13 (Scheme 4, Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scheme 3 As shown in Scheme 3, endo-norbornene ester 9 was prepared by a thermal Diels-Alder reaction of 1-methyl-cyclopentadiene 8 [17] with maleic anhydride, followed by sub-sequent esterification. of Co 2 (CO) 8 atures (120°C) resulted in further increase in the selectivity (12e/13e 12:88, entry 11). [20] Norbornene ester 9 was then employed in NMO-promoted Pauson-Khand reactions with terminal alkynes 11 to give regioisomeric enones 12 and 13 (Scheme 4, Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…

Keywords: Pauson-Khand reaction / Cyclopentenones 1-Methyl-norbornene ester 9 and 1-methyl-2,3-diazabicyclo[2.2.1]heptene ester 10 were employed in intermolecular Pauson-Khand reactions with various terminal alkynes 11af to give the dimethyl 1-methyltricyclo[5.2.1.0 5,9 ]dec-7-en-6one 2,3-dicarboxylates 12 and 13, and diethyl 2,3-diaza-1methyltricyclo[5.2.1.0 5,9 ]dec-7-en-6-one 2,3-dicarboxylates 14 and 15, respectively. It has also been found that other transition metals such as Fe, [2] Ru, [3] Rh, [4] Ni, [5] Cr, [6] Mo, [7] W, [8] Ti, [8] and Zr [9] can be used for the same purpose. For 2-methyl-3-bu-Transition-metal-catalysed co-cyclizations, in particular the Pauson-Khand reaction, can be considered as valuable tools in organic synthesis.

…”
mentioning
confidence: 99%
“…We have previously studied the Pauson-Khand reaction of these substrates with a combination of Cp 2 TiCl 2 /Mg. 8 Herein, we report an unprecedented finding that the choice of Me 2 Zn or Et 2 Zn has dramatic influence on the reaction of 1,6-enynes with the Ni II /R 2 Zn (R = Me or Et) combination. Using a combination of different Ni II complexes and Me 2 Zn, we unexpectedly found that the [2+2+2+2]-type products 2 or the [2+2+2]-type products 3 were selectively obtained in good to excellent yields, while the reductive cyclization products 4 were exclusively formed when only 0.6 equivalents of Et 2 Zn were used as the reductant.…”
mentioning
confidence: 96%
“…It is worth mentioning that excellent regioselectivity could be obtained in the formation of 3a with the two phenyl groups at meta positions, which was confirmed by X-ray crystallographic analysis. 13 Regretably, the use of solvents with weaker coordinating ability, the employment of other Ni salts or the adoption of a larger catalyst loading [20 mol% of Ni(acac) 2 ] 14 all failed to promote the formation of the [2+2+2+2]-type product 2a (Table 1, entries [4][5][6][7][8][9][10][11]. Notably, although mechanistically a catalytic amount of Me 2 Zn should be enough to effect the reaction, the reaction failed to proceed when less than 1 equivalent of Me 2 Zn was used.…”
mentioning
confidence: 99%
“…Formation of the corresponding C Y X ML n ( 1 ) carbonyl compound by treatment of the metallacycles with carbon monoxide or isocyanides [1±3] and the equivalent reaction with triphosgene (OC(OCCl 3 ) 2 ) [4] should be the most representative and useful entry to this reaction [Eq. (1); ML n ZrCp 2 , TiCp 2 , Ti(OiPr) 2 ; CXY CO]. However, other variations of the reaction are notably limited.…”
mentioning
confidence: 99%